1957-2007 : 50 years of higher order programming languages - Lovrenčić, Alen (Array, 2009)
Abstract: Fifty years ago one of the greatest breakthroughs in computer programming and in the history of computers happened -- the appearance of FORTRAN, the first higher-order programming language. From that time until now hundreds of programming languages were invented, different programming paradigms were defined, all with the main goal to make computer programming easier and closer to as many people as possible. Many battles were fought among scientists as well as among developers around concepts of programming, programming languages and paradigms. It can be said that programming paradigms and programming languages were very often a trigger for many changes and improvements in computer science as well as in computer industry. Definitely, computer programming is one of the cornerstones of computer science.